Repensar la democracia participativa en el Perú - Vásquez Castillo, Yeison; Godoy Boy, Fanny (Pontificia Universidad Católica del Perú, 2021)
In Peru, participatory democracy includes descriptive notions, typical of deliberative democracy, a concept that has not been developed, and that could be the cause of its attrition and incorrect operation. This article questions the emergence and institutionalization of participatory democracy and proposes a research framework that allows identifying the quality of participation and deliberation. Finally, some guidelines are given that seek to lay the foundations for an approach that restructures citizen participation: Engineering of citizen participation.

En el Perú la democracia participativa incluye nociones descriptivas, propias de la democracia deliberativa, un concepto que no ha sido desarrollado y que podría ser causa de su desgaste e incorrecto funcionamiento. Este artículo cuestiona el surgimiento e institucionalización de la democracia participativa y propone un marco de investigación que permita identificar la calidad de la participación y de la deliberación. Finalmente, se trazan algunos lineamientos que buscan sentar las bases de un enfoque que reestructure la participación ciudadana: una ingeniería de la participación ciudadana.
Re-thinking participatory democracy in Peru
Keywords: Democracy; Participatory democracy; Deliberative democracy; Participation engineering and participatory democracy policies; Democracia; Democracia participativa; Democracia deliberativa; Ingeniería de la participación y políticas de democracia participativa; https://purl.org/pe-repo/ocde/ford#5.04.00